Comparative Study for Citrus Fruits Phytochemical Screening and In-vitro Antioxidant Activity - AL-KHALIFA, IHAB IBRAHIM; Rand A. Aziz; Mohammed K.Abbas; Mohammed M. Fadhil (Iraqi Journal of Pharmaceutical Sciences, 2023)
Oxidative stress is one of pharmacological & toxicology mechanisms as an important pathological mechanism proposed for many diseases including cancer . Plant components that include antioxidant components are becoming more popular as an alternative to synthetic antioxidants because of their ability to eliminate free-radical intermediates and prevent further oxidation, Citrus genus, which belongs to the Rutaceae family, comprises among of the world’s most frequently harvested crops due to its many nutritional and health advantages. The preliminary phytochemical analysis of the prepared extract shown the presence of several constituents of citrus peels as Alkaloids, Phenolics , Flavonoids and rutin. Moreover , The result of in-vitro antioxidants activity of both citrus species showed that DPPH radical scavenging activity for peel extract demonstrate dose-dependent inhibition with IC50 was calculated (287.32 ug/ml and 341.89 µg/ml) for pomelo & orange respectively compared to IC50 value of vitamin C which was 260.06 µg/ml as standard antioxidant . in conclusion , study results showed that pomelo peel show higher antioxidant activity compared to orange moreover, citrus peel has significant antioxidant qualities and is a potentially rich source of natural antioxidants, and PPE scavenges DPPH and reactive oxygen radicals very effectively.